1908 Ill. Laws 40-41, Regulate Storage of Combustibles--Fireworks, ¶1334, pt. 65 - (:unkn) unknown (General Publisher, 1908)
Amended the powers granted to cities with a population of one hundred thousand or more to regulate and prevent the storage of gunpowder, tar, pitch, resin, coal oil, benzine, turpentine, hemp, cotton, nitro-glycerine, petroleum, or other combustible or explosive material.
--
Keywords: GUN POWDER STORAGE